2021
DOI: 10.3389/fonc.2021.745924
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Effects on Seeds of Cancer Survival in Leukemia

Abstract: The cancer metabolic alteration is considered a hallmark and fast becoming a road for therapeutic intervention. Mitochondria have been regarded as essential cell elements that fuel the metabolic needs of most cancer cell types. Leukemia stem cells (LSCs) are a heterogeneous, highly self-renewing, and pluripotent cell population within leukemic cells. The most important source of ATP and metabolites to fulfill the bioenergetics and biosynthetic needs of most cancer stem cells is the mitochondria. In addition, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 113 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…Of note, mitochondria are the chief site of ROS production, also the epicenter for autophagy and cell death. In abnormal circumstances such as cancer, infection, or derailed cell cycle, the ATP demand will be higher, which eventually forces the cell to synthesize ATP at a higher rate, which would result in excessive ROS generation ( El-Shaqanqery et al, 2021 ). The higher redox threshold of cancer cells indicates that mitochondria acclimatize to higher ROS concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, mitochondria are the chief site of ROS production, also the epicenter for autophagy and cell death. In abnormal circumstances such as cancer, infection, or derailed cell cycle, the ATP demand will be higher, which eventually forces the cell to synthesize ATP at a higher rate, which would result in excessive ROS generation ( El-Shaqanqery et al, 2021 ). The higher redox threshold of cancer cells indicates that mitochondria acclimatize to higher ROS concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Additional metabolomic studies are needed to describe the conditions that drive leukemic cells to choose which TCA source contributes most to this OXPHOS activity because both amino acid ( 104 ) and fatty acid ( 105 ) oxidation have been implicated, demonstrating a high adaptability of their metabolism to ambient conditions. Hence, this metabolic flexibility is starting to be depicted in all the populations that we previously described—bulk cells ( 106 ), LSC ( 107 ) and chemoresistant cells ( 108 )—and it is important to consider because it hinders the possibility of using metabolism as a therapeutic target ( 109 ).…”
Section: Metabolism In Leukemia: Not As Simple As Originally Thoughtmentioning
confidence: 99%
“…Thus, it has been shown that calix [4]arene chalcone amide C-1011 is able to suppress the viability of 4T1 breast adenocarcinoma cells depending on their genetic context associated with the degree of malignancy. Mitochondria have been regarded as essential cell elements that fuel the metabolic needs of most cancer cell types [21]. Currently, it is well established that highly aggressive cancer cells rely on glycolysis instead of mitochondrial oxidative phosphorylation of glucose, and one marker of this metabotype known as the Warburg effect is a decrease in mitochondrial transmembrane potential [22][23].…”
Section: Resultsmentioning
confidence: 99%